Effects of aerobic exercise and progressive muscle relaxation on migraine - Maryum Naseer Butt; Misbah Maryum; Imran Amjad; Omer Jamsheed khan; Liaqat Awan (Journal of the Pakistan Medical Association, 2022)
Objectives: To determine the effect of aerobic exercises and progressive muscle relaxation in migraine patients. Method: The quasi-experimental study was conducted at the Sheikh Khalifa Bin Zayed Al Nayhan Hospital / Combined Military Hospital, Muzaffarabad, Azad Jammu and Kashmir, from February to July 2017, and comprised migraine patients of either gender aged 20-50 years. They were divided into experimental and control group. Experimental group A received supervised exercises protocol, including aerobic exercise (stationary bicycle) 30min with 10min warm-up and 5min cool-down followed by progressive muscle relaxation for 15min 3 times a week for 6 weeks along with prophylactic medicine. The control group received prophylactic medicines flunarazine 5mg twice daily, inderal 10mg thrice daily and nortriptyline 25mg at night. Patients were assessed using Numeric Pain Rating Scale, Migraine Disability Assessment Scale, Headache Disability Index, Headache Impact test-6 and the Central Sensitisation Inventory at baseline, midline and at the completion of intervention. Data was analysed using SPSS 21. Results: Of the 28 patients, there were 14(50%) in each of the two groups. Overall, there were 24(85.7%) females and 4(14.3%) males with a mean age of 29.7±10 years. There were significant improvements in all parameters in both the groups, but group A had significantly better outcome post-inervention (p<0.05). Conclusion: Prophylactic medicine, aerobic exercises and progressive muscle relaxation, when used together, were found to be effective means of intervention for migraine. Key Words: Aerobic exercises, CSI, HDI, HIT-6, Migraine, MIDAS, PMR.